2016
DOI: 10.1080/14616696.2016.1268703
|View full text |Cite
|
Sign up to set email alerts
|

Women at risk: the impact of labour-market participation, education and household structure on the economic vulnerability of women through Europe

Abstract: While increasing female employment has contributed to reducing gender\ud inequality, it has also exposed women to higher economic insecurity. The\ud contribution of this paper is to understand the social conditions that might\ud expose women to economic insecurity in different European cities. Specific\ud aspects have been considered: (a) reduced (part time) work, (b) hampered\ud labour-market participation (unemployment, involuntary inactivity due to care\ud tasks), (c) different household structures (single/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 40 publications
2
11
0
Order By: Relevance
“…Confirming the results from previous investigations [16,32], economic insecurity is a phenomenon that is widespread across Europe, and that affects more women than men, as shown in Table 3. As already discussed, provided the measure of economic vulnerability occurs at the household level it is not possible to clearly identify a gender effect among individuals who live in a couple.…”
Section: The Phenomenon Of Economic Insecurity In the Six Countriessupporting
confidence: 78%
See 3 more Smart Citations
“…Confirming the results from previous investigations [16,32], economic insecurity is a phenomenon that is widespread across Europe, and that affects more women than men, as shown in Table 3. As already discussed, provided the measure of economic vulnerability occurs at the household level it is not possible to clearly identify a gender effect among individuals who live in a couple.…”
Section: The Phenomenon Of Economic Insecurity In the Six Countriessupporting
confidence: 78%
“…First, the Mediterranean cluster was very ambiguous: Spain and Italy showed more differences than similarities, and Italy was actually more similar to the United Kingdom in the case of women in a couple, confirming previous empirical results [16]. The results of the present study also revealed that two countries showed strong segmentation by education level, and the role of labour market participation in these instances was clear.…”
supporting
confidence: 79%
See 2 more Smart Citations
“…in Spain (Durán 1999;Tobío 2001;Del Campo and Rodríguez-Brioso 2002;Gumà et al 2015;Kasearu et al 2017). In line with these reflections, a recent research that coped with working-age population across 12 European countries (Spain was not included; Sandström and Karlsson 2019) showed tenuous or non-existent association between education and solo living in more gender-egalitarian countries whereas the opposite tend to occur in less gender egalitarian countries.…”
Section: Discussionmentioning
confidence: 88%